Penggunaan Model Pembelajaran Project Based Learning pada Mata Pelajaran Bahasa Indonesia Tema Aku untuk Meningkatkan Hasil Belajar Siswa Kelas IV SD Negeri 166/x Pandan Jaya Semester Ganjil Tahun Pelajaran 2022/2023 - Mamik Rahayu (Departement of Mathematics Education, 2022)
This study aims to disclose information and discuss the use of the Project Based Learning Learning Model in Indonesian Subjects with My Theme to Improve Learning Outcomes of Grade IV Students at SD Negeri 166/X Pandan Jaya Odd Semester in the 2022/2023 Academic Year. This research is included in the type of classroom action research (CAR). This research was conducted at SD Negeri 166/X Pandan Jaya. This research was conducted at SD Negeri 166/X Pandan Jaya. When this research was carried out in the odd semester of the 2022 - 2023 school year which began in July 2022. The subjects in this study were 25 grade IV students. The research procedure consisted of two cycles with four research stages starting from planning, implementing, observing and reflecting. Data collection in this study was carried out using res, field notes, observation and documentation. The data analysis technique used in this study is to use the percentage formula. The results of this study are to use the Project Based Learning Learning Model in Indonesian Subjects with My Theme to Improve Learning Outcomes of Grade IV Students at SD Negeri 166/X Pandan Jaya Odd Semester in the 2022/2023 Academic Year. This can be seen from the students' learning completeness which always increases starting in the pre-cycle, cycle I and cycle II, namely by 28%, 60% and 92%.